A Sample Preparation Protocol for High Throughput Immunofluorescence of Suspension Cells on an Adherent Surface. (July 2020) - Bäckström, Anna; Kugel, Laura; Gnann, Christian; Xu, Hao; Aslan, Joseph E.; Lundberg, Emma; Stadler, Charlotte
Imaging is a powerful approach for studying protein expression and has the advantage over other methodologies in providing spatial information in situ at single cell level. Using immunofluorescence and confocal microscopy, detailed information of subcellular distribution of proteins can be obtained. While adherent cells of different tissue origin are relatively easy to prepare for imaging applications, non-adherent cells from hematopoietic origin, present a challenge due to their poor attachment to surfaces and subsequent loss of a substantial fraction of the cells. Still, these cell types represent an important part of the human proteome and express genes that are not expressed in adherent cell types. In the era of cell mapping efforts, overcoming the challenge with suspension cells for imaging applications would enable systematic profiling of hematopoietic cells. In this work, we successfully established an immunofluorescence protocol for preparation of suspension cell lines, peripheral blood mononucleated cells (PBMC) and human platelets on an adherent surface. The protocol is based on a multi-well plate format with automated sample preparation, allowing for robust high throughput imaging applications. In combination with confocal microscopy, the protocol enables systematic exploration of protein localization to all major subcellular structures.